2018
DOI: 10.17265/2332-7839/2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity in Pre-school Children: Role of the Teacher during Free Play

Abstract: It has become evident over the past decade that the lack of PA (physical activity) is a major concern for the population at large CDC (Center for Disease Control). This lack is a major reason for the increase in overweight and obese children (USDHHS, 2014). The CDC and the American Heart Association recommend children need at least 60 minutes of play time that is not scheduled PA. The purpose of this research was to examine whether children's PA will increase if teacher activity increases during unstructured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Future research should utilize a validated direct observation tool to measure teachers’ physical activity behaviors within preschool to further investigate ergonomic and physical activity outcomes and relation to children’s physical activity. Furthermore, teachers may have to consider ways in which they can be physically active with children while also being cognizant of how to best sustain their energy and wellness to provide a high quality of education and care (Culpepper & Killion, 2018 ; Hibbs-Shipp et al, 2015 ; Lessard et al, 2020 ). Efforts may be needed to help preschool teachers take part in more restorative physical activity practices (e.g., stretching) that could help reduce pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future research should utilize a validated direct observation tool to measure teachers’ physical activity behaviors within preschool to further investigate ergonomic and physical activity outcomes and relation to children’s physical activity. Furthermore, teachers may have to consider ways in which they can be physically active with children while also being cognizant of how to best sustain their energy and wellness to provide a high quality of education and care (Culpepper & Killion, 2018 ; Hibbs-Shipp et al, 2015 ; Lessard et al, 2020 ). Efforts may be needed to help preschool teachers take part in more restorative physical activity practices (e.g., stretching) that could help reduce pain.…”
Section: Discussionmentioning
confidence: 99%
“…Several environmental factors exist within preschool centers that have been found to be influential on children’s physical activity such as the size of indoor and outdoor spaces, weather, time, play equipment, and child enrollment numbers (Clevenger et al, 2022 ; Copeland et al, 2016 ; Culpepper & Killion, 2018 ; Dwyer et al, 2008 ; Henderson et al, 2015 ; Sisson et al, 2017 ). Additional factors that may influence children’s physical activity are the behaviors of teachers (Culpepper & Killion, 2018 ; Frank et al, 2018 ; Gunter et al, 2012 ). For instance, studies have shown children’s physical activity levels during outdoor play increased when teachers engaged in play with the children (Culpepper & Killion, 2018 ; Frank et al, 2018 ; Gunter et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation